An “Omic” Overview of Fragile X Syndrome - Olivier Dionne; François Corbin (Biology, 2021)
Fragile X syndrome (FXS) is a neurodevelopmental disorder associated with a wide range of cognitive, behavioral and medical problems. It arises from the silencing of the fragile X mental retardation 1 (FMR1) gene and, consequently, in the absence of its encoded protein, FMRP (fragile X mental retardation protein). FMRP is a ubiquitously expressed and multifunctional RNA-binding protein, primarily considered as a translational regulator. Pre-clinical studies of the past two decades have therefore focused on this function to relate FMRP’s absence to the molecular mechanisms underlying FXS physiopathology. Based on these data, successful pharmacological strategies were developed to rescue fragile X phenotype in animal models. Unfortunately, these results did not translate into humans as clinical trials using same therapeutic approaches did not reach the expected outcomes. These failures highlight the need to put into perspective the different functions of FMRP in order to get a more comprehensive understanding of FXS pathophysiology. This work presents a review of FMRP’s involvement on noteworthy molecular mechanisms that may ultimately contribute to various biochemical alterations composing the fragile X phenotype.